Perioperative Optimization of Patients With Neuromuscular Disorders Undergoing Scoliosis Corrective Surgery: A Multidisciplinary Team Approach. Issue 2 (March 2021) - Sedra, Fady; Shafafy, Roozbeh; Sadek, Ahmed-Ramadan; Aftab, Syed; Montgomery, Alexander; Nadarajah, Ramesh
Study Design: Narrative review. Objective: The high rate of complications associated with the surgical management of neuromuscular spinal deformities is well documented in the literature. This is attributed to attenuated protective physiological responses in multiple organ systems. Methods: Review and synthesis of the literature pertaining to optimization of patients with neuromuscular scoliosis undergoing surgery. Our institutional practice in the perioperative assessment and management of neuromuscular scoliosis is also described along with a clinical vignette. Results: Respiratory complications are the most common to occur following surgery for neuromuscular disorders. Other categories include gastrointestinal, cardiac, genitourinary, blood loss, and wound complications. A multidisciplinary approach is required for perioperative optimization of these patients and numerous strategies are described, including respiratory management. Conclusion: Perioperative optimization for patients with neuromuscular disorders undergoing corrective surgery for spinal deformity is multifaceted and complex. It requires a multidisciplinary evidence-based approach. Preadmission of patients in advance of surgery for assessment and optimization may be required in certain instances to identify key concerns and formulate a tailored treatment plan.